2007
DOI: 10.1096/fj.06-7688com
|View full text |Cite
|
Sign up to set email alerts
|

Low expression of COX‐2, reduced cumulus expansion, and impaired ovulation in SULT1E1‐deficient mice

Abstract: The SULT1E1-encoded estrogen sulfotransferase (EST) catalyzes sulfation of estrogen, resulting in its inactivation. Reduced fertility observed in SULT1E1 knockout (KO) female mice has previously been attributed to the deleterious effect of chronic exposure to high levels of circulating estrogen on placental function. We herein suggest that, in addition to placental dysfunction, this phenotype demonstrates that an excess of estrogen impairs ovulation. The role of SULT1E1 in ovulation is suggested by the substan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 50 publications
1
31
0
1
Order By: Relevance
“…The regulation of both Sult1e1 and HSD17b7 2 h after hCG would lead to opposite effects on oestrogen bioavailability. Together, these observations suggest that, in the LRH-1 KD model, oestradiol is not the main component that causes the infertility phenotype, and this is further supported by the fact that mouse models of increased oestrogenic activity do not show complete female infertility (Jablonka-Shariff et al 1998;Gershon et al 2007). The different effect on oestradiol in LRH-1-KD mice compared with granulose cell-specific LRH-1-knockout mice (Duggavathi et al 2008) could be explained by the incomplete and temporal nature of KD of LRH-1 in the LRH-1-KD mice.…”
Section: Discussionmentioning
confidence: 76%
“…The regulation of both Sult1e1 and HSD17b7 2 h after hCG would lead to opposite effects on oestrogen bioavailability. Together, these observations suggest that, in the LRH-1 KD model, oestradiol is not the main component that causes the infertility phenotype, and this is further supported by the fact that mouse models of increased oestrogenic activity do not show complete female infertility (Jablonka-Shariff et al 1998;Gershon et al 2007). The different effect on oestradiol in LRH-1-KD mice compared with granulose cell-specific LRH-1-knockout mice (Duggavathi et al 2008) could be explained by the incomplete and temporal nature of KD of LRH-1 in the LRH-1-KD mice.…”
Section: Discussionmentioning
confidence: 76%
“…It was reported that dominant follicles have greater concentrations of E2 in their follicular fluid in comparison to the subordinate follicles [37,38]. And also, a critical decrease in E2, after the LH surge, is necessary to enable normal ovulation in rodent [39]. Gershon et al demonstrated that estrogen inactivation might allow the LH-induced expression of cyclooxygenase-2 (COX-2) and subsequent C-OE, allowing normal ovulation.…”
Section: Discussionmentioning
confidence: 99%
“…ЦОГ2 запускає сигналізацію простаглан-динів (ПГ) у яєчнику, які синтезуються з арахідонової кислоти [29]. ПГ є загальними медіаторами запальних реакцій, включаючи й овуляцію.…”
Section: оглядиunclassified